Knowledge and awareness among nursing students regarding the COVID-19: a cross sectional study - Joshi, K. P.; Madhura, Leena; Jamadar, Deepak (International Journal Of Community Medicine And Public Health, 2020)
Background: The health care providers are at the front line of the outbreak response of current pandemic of COVID-19 and exposed to hazards that put them at risk of infection. Rapid spread of the COVID-19 pandemic has become a major cause of concern for the healthcare profession in all over the world. All health care professional must stay aware of the latest information on the COVID-19 outbreak. This research paper deals with the knowledge and awareness about COVID-19 among nursing students. Methods: By non-probability snowball sampling method the sample size was 407. Predesigned and pretested questionnaire was used in this study. Questions were related to knowledge and awareness about current COVID-19. The participant was directed to complete the self-report survey by online. The data was tabulated and analysed statistically. MS-Excel and Statistical Package for Social Sciences version 22.0 used for all statistical analysis. Results: A total of 407 nursing students participated in this study. Over all 75.58±3.21 participants showed good knowledge and awareness about COVID-19. Around 87.47% respondents were aware about high risk age group for COVID-19. 83.54% participants were aware about concept of hand hygiene and 83.37% were well aware of PPE for suspected or confirmed COVID-19 cases. Conclusions: The study participants showed adequate basic knowledge and awareness of COVID-19. There is a strong need to implement periodic educational interventions and training programs on infection control practices and other updates of COVID-19 across all healthcare professions including nursing students.